pre calc

posted by .

solve following using "elimination method"

3x^2 + 4y = 17
2x^2 + 5y = 12

  • pre calc -

    Multiply the first equation by 2 and the second equation by 3, and subtract one from the other. That will eliminate the x^2 variable.

    6x^2 + 8y = 34
    6x^2 + 15y = 36

    7 y = 2
    y = 2/7

    2x^2 = 12 - 5y = 12 - 10/7
    = 74/7
    x = sqrt(37/7) = 2.299

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Pre-Calculus

    Solve for x,y,z, & w using the Gauss-Jordan Elimination Method 5x+3y+z+5w=-2 3x+2y+2z+4w=2 2x+4y+3z-3w=-11 4x-3y-2z+2w=-3 Can anyone help me please?
  2. Algebra

    Solving system of linear equations by using the apropiate method name the method and the x,y coordinates 1)X=4y+8 2x-8y=-3 2)3x-7y=6 elimination method 2x+7y=4 (2,0) 3)5x-2y=12 elimination method 3x-2y=-2 (7,23/2) 4)9x-8y=42 elimination …
  3. Pre Calc

    x^2+y=9, x-y+3=0. Need to solve using substitution method.
  4. Algebra/Elimination method

    Solve using the elimination method. If the system has no solution or an infinite number of solutions, state this. -27x - 18y = -180 9x + 6y = 60
  5. Pre-Calc

    Solve the system of equations using either the substitution method or the multiplication/addition method answer: 3x+2y=14 2x-4y=4
  6. Pre-Calc/Trig...

    Solve using any method. 1. 2x^2+5x-3=0 2. -x^2+x+1=0
  7. Algebra 1

    bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
  8. pre-calc

    Solve the system of equations using matrices. Use Gaussian elimination with back- substitution. x+y+z = -5 x-y+3z = -1 4x+y+z = -2
  9. pre-calc

    Solve the system of equations using matrices. Use Gaussian elimination with back- substitution. x+y+z = -5 x-y+3z = -1 4x+y+z = -2
  10. pre-calc - JAI

    Solve the system of equations using matrices. Use Gaussian elimination with back- substitution. x+y+z = -5 x-y+3z = -1 4x+y+z = -2

More Similar Questions